Byron's "Manfred" and the Greek imaginary - Leman, Lucia (2014)
Using Jerome J. McGann’s suggestion that the earliest fragments of Manfred might have been written during his Levantine Tour (c 2 July 1809 – 14 July 1811), this thesis aims to offer a new perspective on Byron’s Manfred, taking into account issues inherent in Byron’s patrician upbringing, his experience of Ottoman Greece, his notion of a Classical tradition, and his previous Byronic heroes. The majority of motifs previously perceived as “Gothic” can thus be seen in a new light, namely, as “Greek”. Another inspiration for a “Greek” reading of Manfred has been the fact that Western-European formative education and the literary canon have been based on works written by fifth-century BC Athenian writers, works which evoke a model of intellectual and political sophistication which I call, “the Greek imaginary” on the basis of its essentially fictive quality. However, the Greek imaginary formed part of a nobleman’s education from the days of fifth-century Athens until well after Byron’s age, by the time of which “Greekness” was a form of noblesse oblige amongst privileged North-Western Europeans, while “Greece” denoted a sense of the (imaginary) origin of Western-European culture. In effect, this thesis offers an insight into Byron’s Greek imaginary, shaped by the poet’s Classical education, his loyalty to the British patrician class, and his choice of reading matter from childhood onwards, as well as by what I call, his “inner Greek landscape”, namely an inner mental construct formed during his Levantine Grand Tour, wherein the “Oriental” Greek landscape was tempered by the literary landscapes of his Classical primers. This study provides a detailed account of the ideological and cultural traditions in which Byron’s intellect was formed, showing how the landscapes of Western Greece and Switzerland were conflated with the literary landscapes of Pausanias, Longinus and English pastoral poetry. The Introduction surveys the Greek imaginary, its historical dissemination, its respective appropriations by the Roman Empire and by North-Western Europeans, especially by British Whigs, and its legacy within British poetry, especially regarding the description of mountain landscapes. Aiming to facilitate an insight into Byron’s formative experiences, the chapter offers a survey of eighteenth-century Philhellenism and its socio-political conditions, namely the institution of the Grand Tour, burgeoning Orientalism, Winckelmann's aesthetic reassessment of the plastic arts (followed by the trends of antiquarianism and the picturesque in British painting) and the French Revolution. Here, I draw an ideological and aesthetic distinction between the Greek imaginary and Gothicism and then I outline Byron's Greek imaginary. Chapter One assesses Byron’s intellectual formation from the time he was taught to read until the moment of his Grand Tour (c 1794 – 1809), reviewing it within the cultural and ideological framework of the British Whigs, whose education was based on the study of Ancient Greek and Latin and whose adult culture displayed the dissemination of tropes taken from Classical texts, for example the Eleusinian and Bacchic Mysteries, within Whig gentlemen’s clubs, and pastoral and travel writing. In effect, both Byron’s comprehensive knowledge of Ancient Greek history and literature and his Enlightened Orientalism can be read as a product of his patrician upbringing. Chapter Two follows the movements of Byron and John Cam Hobhouse in Western Greece prior to their arrival in Athens (c October – December 1809) with Pausanias and the Arnaout servants of the tyrant Ali Pasha as their guides and protectors. It is argued that Byron’s “inner Greek landscape” (a collection of motifs which appear in all of his works from Childe Harold’s Pilgrimage and which I see epitomized by Manfred) was formed during the initial three months of his Grand Tour. Here, various elements of that “landscape”, both topographical as well as literary and metaphorical, are established. This chapter also surveys Byron’s antiquarianism, scholarly Orientalism (namely his studies in Romaic philology) and his divided attitude to the abstract legacy of Classical Greece and the contemporary Greeks. The last issue was epitomized by the concepts of the “mark of Cain” and the Byronic hero’s tragic love for his other, (apparently a native of Ottoman Greece), which I see as the two leitmotifs of Byron's poetic fictions featuring the Byronic hero (namely from Childe Harold’s Pilgrimage until Manfred). The chapter also charts the Platonic notion of eros and a quest for the Kalon, pivotal to Byron's concept of love as absent presence, and key to the Byronic hero's self-torture and self-sufficiency. Chapter Three considers the events preceding and surrounding the composition of Manfred (April 1816 – May 1817), following Byron on his second Continental Tour, where his Greek imaginary was displaced onto the Belgian plains, German hills, Swiss mountains, the city-state of Venice and the Mekhitarist monastery of St Lazarus. This chapter observes the impact of Thomas Taylor's Neo-Platonist treatise, A Dissertation of the Eleusinian and Bacchic Mysteries, matched by the impact of Byron’s new friend, the poet Percy Bysshe Shelley, on Byron's subsequent composition of Manfred. The influences of Taylor and Shelley are evident in Byron's respective views of suffering in life as a part of the soul’s philosophical journey, and in his approach to the Promethean myth, Classical democracy, and the Gothic trope, the last serving as an excuse for a series of sceptical discussions culminating with the Diodati contest. Lastly, this chapter traces the influence of Shelley and his friend Peacock on Byron's reassessment of the Promethean and Christian myth during the time of his collaboration with the Mekhitarist monks of St Lazarus, when he was simultaneously writing Manfred and translating the apocryphal words of St Paul the Apostle, which can be read as approving of Manfred’s ultimate self-sufficiency. Following insights from the previous chapters, Chapter Four provides a close reading of Manfred, assessing the play as a form of simultaneous dialogue between Aeschylus, Plato, and Byron’s own hero. While the hero’s musings and monologues are seen as a reiteration of Aeschylus’ Prometheus Bound, and while his notion of a (deflected) eros seems inherited from the first two cantos of Childe Harold’s Pilgrimage and Oriental Tales, the plot of the play seems to follow the course of an initiation rite (theoria) evoked in Plato’s (and Taylor’s) notion of the Eleusinian and Bacchic mysteries. During the course of the play, Manfred is seen as an initiate reclaiming his lost eros, which then enables him to behold the highest good, the Kalon, and to come to terms with the fact that he was, and will be, his own destroyer, whereby displacing the Almighty as the (unjust) ruler of the Universe. In the conclusion, I recapitulate the key terms and concept of my thesis, the function and dissemination of Manfred as an ontologically subversive and politically ambitious reading play and as a contemporary myth. Lastly, the conclusion outlines the significance of Manfred within Byron’s subsequent artistic development by ushering in a shift of Byron’s focus onto collective and cosmic forces, and a more and more impersonal hero.